DIAGNOSIS AND TREATMENT OF AIRWAY HYPERREACTIVITY IN FREQUENTLY ILL CHILDREN AND ADOLESCENTS (Journal of Multidisciplinary Sciences and Innovations, 2025)
This study is aimed at examining the methods of diagnosing and treating airway hyperreactivity (AHR) in children and adolescents frequently affected by respiratory tract infections. Diagnosis was made based on clinical, spirometric, and provocation tests, and the effectiveness of medications was evaluated. The obtained results made it possible to develop strategies for early detection and effective treatment of AHR.